Nitrogen Fertilizer Adjustment in Legume-Cereal Rotations - Shewangizaw, Beza; Agegnehu, Getachew; Desta, Gizaw; Legesse, Gizachew; Desalegn, Henok; Tigabie, Abiro (International Crops Research Institute for the Semi-Arid Tropics, 2025)
Sustainable food production is one of the major global challenges, exacerbated by climate change, increasing population, and natural resource degradation, including soil degradation and loss of biodiversity (Pretty and Bharucha, 2014; Vanlauwe et al., 2014). Cropping systems that specialize in one or two crops, with little attention to crop diversity, may lead to biological and physical soil degradation (Kirschenmann, 2002; Tanaka et al., 2010). Annual cropping systems, which include diverse crops such as cereals, legumes, and oilseeds, may be economically viable options for farmers. Diversifying crops in cropping systems also influences the soil environment and diversity of soil organisms (Williams et al., 2023; Yang et al., 2020). It is crucial to consider the synergistic or antagonistic relationships of crops in cropping systems for sustainability and resilience in agricultural systems (Kirschenmann, 2007).